2016
DOI: 10.1016/j.immuni.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Coordinate the Development and Homeostasis of Organ-Specific Regulatory T Cells

Abstract: SUMMARY Whereas antigen recognition mediated by the T cell receptor (TCR) influences many facets of Foxp3+ regulatory T (Treg) cell biology, including development and function, the cell types that present antigen to Treg cells in vivo remain largely undefined. By tracking a clonal population of Aire-dependent, prostate-specific Treg cells in mice, we demonstrated an essential role for dendritic cells (DCs) in regulating organ-specific Treg cell biology. We have shown that the thymic development of prostate-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 47 publications
11
88
2
Order By: Relevance
“…Among these 72 candidate genes, genes that control cancer cell stemness (including NF-κB1 [34], IL-1β [35], and CCR7 [36, 37]) and that scored significantly in the screen were selected, thereby demonstrating the effectiveness of the screen. However, genes that control pluripotency (including IL-6, and STAT3 [38]) did not score significantly in the screen possibly reflecting insufficient knockdown, redundancy, or that their role in CSC identity did not involve OCT4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 72 candidate genes, genes that control cancer cell stemness (including NF-κB1 [34], IL-1β [35], and CCR7 [36, 37]) and that scored significantly in the screen were selected, thereby demonstrating the effectiveness of the screen. However, genes that control pluripotency (including IL-6, and STAT3 [38]) did not score significantly in the screen possibly reflecting insufficient knockdown, redundancy, or that their role in CSC identity did not involve OCT4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For selection to occur, developing thymocytes must interact with an array of thymic APCs (cTECs, mTECs, B cells, macrophages and DCs) that present thymically derived and peripherally transferred antigenic epitopes (3, 6, 7). In our study, we find that ectopic insulin (InsB 9–23 ) and agonist insulin (R22E) expression restricted to bone marrow derived APCs protect high and low affinity insulin specific TCR Rg mice from autoimmune diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that bone marrow derived APCs, including DCs, play a critical role in tTreg development by both AIRE-dependent and independent mechanisms (7). Foxp3 + tTreg development occurs in a restricted thymic niche regulated in part by the presence of APCs presenting cognate antigen (5, 51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-antigens present in the thymus, either through Autoimmune Regulator (AIRE)-mediated tissue specific antigen expression or circulating Sirp1 + DCs, drive the development of tTregs [13][14][15][16][17]. Tregs can also develop in the periphery from mature CD4 + cells through non-inflammatory exposure to low-dose antigens.…”
Section: Tregs Are Critical Mediators Of Peripheral Tolerancementioning
confidence: 99%